Lessons from the Field Developing and Implementing the Qatar Student Assessment System, 2002-2006 - Gonzalez, Gabriella C. (RAND Corporation, 2009)
Central to Qatar's education reform was the development of internationally benchmarked curriculum standards and standards-based assessments in four subjects: Arabic, English as a foreign language, mathematics, and science. This report recounts the development of Qatar's standards-based student assessment system, providing important lessons learned for Qatar and other countries that are seeking to implement similar measures on a large scale.